LA COMPRA DEL VIZCONDADO DE RUEDA EN 1393: THE PURCHASE OF RUEDA VISCOUNTY IN 1393 - Navarro Espinach, Germán; Villanueva Morte, Concepción; Sola Arnal, Alejandro Jesús (Aragón en la Edad Media, 2025)
La transcripción de una copia inédita del siglo XIX que reproduce la compra del vizcondado de Rueda en 1393 por el noble lope Jiménez de Urrea sirve de punto de partida para estudiar los orígenes de dicho señorío desde su fundación en 1366 hasta la segunda mitad del siglo XvI según los datos disponibles en diversas fuentes sobre sus villas y términos de Rueda y Épila.Palabras clave: vizcondado de Rueda, siglos XIV-XVI, señorío, Aragón, linaje de Urrea, Rueda, Épila.The transcript of an unpublished copy nineteenth century that reproduces the purchase of Rueda viscounty in 1393 by the noble lope Jiménez de Urrea serves as a starting point to explore the origins of the manor since its foundation in 1366 until the second half of sixteenth century according to available data from various sources about their villages and terms of Rueda and Épila.Keywords: Rueda viscounty, XIV-XVIth centuries, manor, Aragon, lineage of Urrea, Rueda, eÉpila